Analysis of Increasing Repurchase Intention on PT. Cisarua Mountain Dairy (Cimory) in East Java: Analisis Peningkatan Repurchase Intention Pada Produk PT. Cisarua Mountain Dairy (Cimory) di Jawa Timur - Rahmadhani, Debi; Sukmono, Rita Ambarwati (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to analyze, inform and explain about the increase in Repurchase Intention on PT. Cisarua Mountain Dairy (Cimory) in East Java. The method used in this research is a quantitative approach. Sampling in this study was conducted through a questionnaire with non-probability sampling technique with purposive sampling method and the number of samples in this study were 200 respondents. The data analysis technique used in this research is the measurement of the inner model and outer model using the SmartPLS 3.0 program. The results showed that Brand Experience had a positive and significant effect on Customer Satisfaction, and Customer Satisfaction had a positive and significant effect on Repurchase Intention.